Next-generation sequencing methylation profiling of subjects with obesity identifies novel gene changes. Issue 1 (December 2016) - Day, Samantha; Coletta, Richard; Kim, Joon; Campbell, Latoya; Benjamin, Tonya; Roust, Lori; De Filippis, Elena; Dinu, Valentin; Shaibi, Gabriel; Mandarino, Lawrence; Coletta, Dawn
Abstract Background Obesity is a metabolic disease caused by environmental and genetic factors. However, the epigenetic mechanisms of obesity are incompletely understood. The aim of our study was to investigate the role of skeletal muscle DNA methylation in combination with transcriptomic changes in obesity. Results Muscle biopsies were obtained basally from lean (n = 12; BMI = 23.4 ± 0.7 kg/m2 ) and obese (n = 10; BMI = 32.9 ± 0.7 kg/m2 ) participants in combination with euglycemic-hyperinsulinemic clamps to assess insulin sensitivity. We performed reduced representation bisulfite sequencing (RRBS) next-generation methylation and microarray analyses on DNA and RNA isolated fromvastus lateralis muscle biopsies. There were 13, 130 differentially methylated cytosines (DMC; uncorrectedP < 0.05) that were altered in the promoter and untranslated (5' and 3'UTR) regions in the obese versus lean analysis. Microarray analysis revealed 99 probes that were significantly (correctedP < 0.05) altered. Of these, 12 genes (encompassing 22 methylation sites) demonstrated a negative relationship between gene expression and DNA methylation. Specifically, sorbin and SH3 domain containing 3 (SORBS3) which codes for the adapter protein vinexin was significantly decreased in gene expression (fold change −1.9) and had nine DMCs that were significantly increased in methylation in obesity (methylation differences ranged from 5.0 to 24.4 %). Moreover, differentially methylated region (DMR) analysis identified a region in the 5'UTR (Chr.8:22, 423, 530–22, 423, 569) of SORBS3 that was increased in methylation by 11.2 % in the obese group. The negative relationship observed between DNA methylation and gene expression for SORBS3 was validated by a site-specific sequencing approach, pyrosequencing, and qRT-PCR. Additionally, we performed transcription factor binding analysis and identified a number of transcription factors whose binding to the differentially methylated sites or region may contribute to obesity. Conclusions These results demonstrate that obesity alters the epigenome through DNA methylation and highlights novel transcriptomic changes in SORBS3 in skeletal muscle.